Crustal Formation on a Spreading Ridge Above a Mantle Plume: Receiver Function Imaging of the Icelandic Crust. Issue 6 (29th June 2018) - Jenkins, J.; Maclennan, J.; Green, R. G.; Cottaar, S.; Deuss, A. F.; White, R. S.
Abstract: Iceland sits astride a mid‐ocean ridge underlain by a mantle hot spot. The interplay of these two geological processes has the potential to generate a complex and laterally variable crustal structure. The thickness of the Icelandic crust is a long running and controversial debate, with estimates ranging from a thin 20‐km crust to a thick 40‐km crust. We present new images of the first‐order seismic discontinuity structure of the Icelandic crust based on a joint inversion of receiver function and ambient noise‐derived surface wave dispersion data. Inversion results are validated through comparison to receiver functions multiphase common conversion point stacks across the densely instrumented Northern Volcanic Zone. We find a multilayered crustal structure consisting of a 6‐ to 10‐km‐thick upper crust underlain by either one or two discontinuities. The shallower discontinuity is found at depths of ≈20 km throughout Iceland. The deeper discontinuity is only present in some regions, defining the base of a lens‐like lower layer with maximum depths of 44 km above the center of the mantle plume. Either of these two discontinuities could be interpreted as the seismic Moho, providing an explanation why previous estimates of crustal thickness have diverged. Such structure may form via underplating of a preexisting oceanic crust as has been hypothesized in other ocean island plume settings. However, we demonstrate with a simple petrological model that variability in seismic discontinuity structure can also be understood as a consequence of compositional variation in melts generated with distance from the plume center. Plain Language Summary: When tectonic plates pull apart, magma wells up between them forming new oceanic crust. Iceland sits astride one of these mid‐ocean ridges, but unlike most others which are found on the ocean floor, it is raised above sea level. This is caused by a hot area of the Earth's mantle raising the area up, thought to be caused by a mantle plume (a convective upwelling rising from the Earth's core). In this study we try and understand what crust formed in this special setting, where mid‐ocean ridge and mantle plume interact, looks like. We make observations of the Icelandic crust using distant earthquakes that are recorded in Iceland, extracting information that earthquake signals carry about the material they travel through on their journey through the Icelandic crust. This gives us a new picture of Iceland's crust: it is much thicker than normal mid‐ocean ridge crust, thickest in the center above the plume and thinning outward, and is made up of several layers. By analyzing crystal content of lavas erupted in Iceland at different distances from the plume, we construct a model that explains the structure we observe by variation in the types of magma available for crustal formation in different locations. Key Points: Seismic discontinuity structure of the Icelandic crust is imaged using receiver functions and surface wave dispersion data We image an approximately 20‐km‐thick layer underlain by a lens of higher‐velocity material to depths of 44 km Imaged structure may form via magmatic underplating or lateral variability in supplied melt composition with distance from plume center